CYBER DEFAMATION IN INDONESIA'S NATIONAL CRIMINAL CODE: AN ANALYSIS OF THE NEW PROVISIONS - Abdaud, Faisal; Haris, Oheo Kaimuddin (Universitas Syiah Kuala, 2024)
This article investigates the impact of cyber defamation regulations within Indonesia's National Criminal Code (NCC), a topic worthy of investigation due to the significant changes in the definition and scope of cyber defamation offenses following the NCC's enactment. Through a normative legal research approach, the study examines legal rules, principles, and doctrines, employing both statutory and conceptual analyses. The findings indicate that the NCC's provisions on cyber defamation, as lex generalis, take precedence over Article 27 paragraph (3) of the Information and Electronic Transactions (ITE) Act, while Article 27A of the Second Amendment to the ITE Law remains in provisional effect until the NCC's full implementation in 2026. Notably, cyber defamation is addressed in seven articles (Articles 433-439) within the NCC, which also specifically cover defamation against the President, government, and state institutions. To mitigate potential ambiguities, the development of implementing regulations is recommended to clarify the application of these NCC defamation provisions. The changes align with established legal principles, ensuring a coherent and effective regulatory framework. This article contributes to a deeper understanding of the NCC's new cyber defamation provisions by analyzing their scope, implications, and the need for implementing regulations to ensure consistent and effective application.